Perbandingan Vulnerability Assesment Menggunakan Owasp Zap dan Acunetix Pada Sistem Informasi Repositori Politeknik Negeri Indramayu - Riyan Farismana; Dian Pramadhana (Pusat Riset dan Inovasi Nasional, 2023)
The security of web-based systems is an important thing that an organization needs to pay attention to, considering that currently all organizational business processes rely on the web to store and process their data. POLINDRA is also not left behind, which uses web technology to store and process a list of student work repositories into a web-based information system. This requires simultaneous testing and risk assessment to determine the level of existing risks and vulnerabilities. The results of the vulnerability assessment to determine security gaps carried out in the scientific work repository information system on the sista.polindra.ac.id page using two different tools, namely Owasp Zap and Acunetix, have several different results. On Owasp Zap, there were 22 warnings, while Acunetix found 499 warnings. Even though the number of alerts using Acunetix is greater, the alert type results are not as complete as Owasp Zap, which produces 22 alerts, while Acunetix only produces 10 alerts.